Effect of wood residues on the growth of Ganoderma lucidum - Cortina-Escribano, Marta; Veteli, Pyry; Linnakoski, Riikka; Miina, Jari; Vanhanen, Henri (Societas Mycologica Fennica, 2020)
Sawmill industries generate considerable amounts of low value wood residues. Fungal decomposition of lignocellulosic biomass allows the conversion of wood residues into valuable products. The selection of the most suitable fungal strains and media are essential to optimise the bioconversion of wood residues and serves as a basis for mushroom cultivation industries. The aim of this study was to find the best combinations of Ganoderma lucidum strains and substrate media to optimise the cultivation of the fungus. Mycelial growth and culture characteristics of G. lucidum isolated from Betula pubescens and Picea abies in Finland were tested on agar media containing different wood residues. These included Betula sp., Populus tremula, Larix sp., Pinus sylvestris, Alnus incana and P. abies sawdust, which were added to malt extract agar, potato dextrose agar and water agar. The results showed significant differences in the mycelial growth between all interaction levels (agar media, wood species and fungal strain). The addition of malt extract significantly enhanced the growth of the fungus in comparison to potato dextrose or water agar. The wood sawdust most suitable for mycelial growth was Betula sp., followed by P. tremula. Strains originally isolated from P. abies also presented higher mycelial growth in media with hardwood sawdust. These findings demonstrate that Betula sp. and P. tremula sawdust stimulate the growth of G. lucidum. Thus, it is possible to cultivate the fungus on a variety of wood residues from sawmill industries.
Keywords: bioconversion; Ganoderma lucidum; lignocellulosic biomass; mushroom cultivation; mycelial growth; mycelial morphology; wood residues